Treatment options for chronic hypotony: a scoping review protocol - Harry Petrushkin; Rana Khalil; Desta Bokre; Karla Orsine Murta Dias; Aman Sutaria; Diya Shah (BMJ Open)
Introduction Chronic ocular hypotony (low intraocular pressure (IOP)) is a potentially sight-threatening condition. Although there is some controversy as to what constitutes non-physiological IOP, generally it is accepted as an IOP of 6.5 mm Hg or less, measured on three separate occasions and lasting for at least 3 months. There is a paucity of data in the literature describing the management of this potentially blinding condition. As such, there is no standardised treatment regime available and no consensus on expected visual prognosis.Methods and analysis The protocol for this scoping review will follow best practice as outlined by the JBI Scoping Review Methodology Group. This review will employ the population, concept, and context model for synthesis of the review questions. Databases searched will be Ovid Medline, Ovid Embase, The Cochrane Central Register of Controlled Trials, Web of Science and Scopus databases, as well as reference lists of relevant articles and the grey literature. Key concepts identified for conducting the literature search will be ‘Ocular hypotony’, ‘medication’ and ‘surgery’. Eligibility criteria include all adults undergoing medical or surgical treatment for chronic ocular hypotony. In order to validate this search strategy, we performed a sample search on Ovid Medline from 1946 to February 2024. Following the selection process, a custom form was developed in Microsoft Excel for data charting. We intend to summarise the data using a narrative model, with the study findings grouped based on similarities in the type of treatment and outcomes assessed.Ethics and dissemination Ethical approval was not required, as our review will only include published data. We will publish the review in an open-access, peer-reviewed journal and publicise our findings at international meetings.